Specialities of professional etiquette and business protocol in France - Veselá, Jana; Gullová, Soňa, 1954-; Müllerová, Františka, 1948-; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2009)
This theses describes specialities of professional etiquette and business protocol in France. The aim of this theses is to provide comlete view of rules of behaviour in business relations with French business partners primarily because of the fact that France has become, during last 15 years, an importat business partner of the Czech Republic. The first chapter defines terms professional etiquette and business protocol in general and chracterizes basic French qualities. The second chapter is dedicated to specialities of professional etiquette in France. It is focused on character of French companies, work etiquette, business trips and business negotiations with French business partners as well. The third chapter is concentrated on business protocol in France which means the rules of etiquette that should be followed during business negotiations with the French. It describes forms of introdictions, addressings, the rules of written and oral etiquette as well as the rules of dressing and dining. The fourth chapter is devoted to France and to the Czech-French business relations. The aim of this chapter is to shortly characterize the situation of France in the international trade and developing business relations between France and the Czech Republic.
Vedoucí práce: Soňa Gullová
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Způsob přístupu: Internet
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2010
Rok obhajoby 2010
Keywords: mezinárodní obchod [obor bakal. práce]; bakalářské práce; bachelor's theses